Cervical extension of pancreatic pseudocyst an unusual entity - Charutha, Roshil; Joshi, Madhur Arun; Joshi, Sampada (International Surgery Journal, 2024)
Pancreatic pseudocyst is a common complication that occurs following acute or chronic pancreatitis. Although the common location of pseudocyst is lesser sac, extension of pseudocyst can occur into mesentery, retroperitoneum, inguinal region, pleura and lung. Extension of pseudocyst into mediastinum and cervical spaces is extremely rare. Mediastinal extension of pseudocyst is a rare occurrence reported in fewer than 100 cases. Cervical extension of pseudocyst is even rarer. Due to the rarity of the condition, there is a lack of uniform treatment protocols which poses a challenge in the management of this condition. Here we report a rare case of bilateral cervical extension of ruptured pseudocyst and its management.